2018
DOI: 10.3390/app8112134
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Identification of Lepidii Seu Descurainiae Semen and Adulterant Seeds Using Microscopic Analysis

Abstract: Lepidii seu Descurainiae Semen, the dried ripe seeds of Descurainia sophia (L.) Webb ex Prantl or Lepidium apetalum Willd., is used widely as a traditional herbal medicine in Northeast Asia. However, seeds of a number of other species have been misidentified as Lepidii seu Descurainiae Semen, and are therefore misused because of morphological similarities among the seeds of these species. To accurately identify Lepidii seu Descurainiae Semen, we investigated the morphology, mucilage reaction, and micromorpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
(39 reference statements)
1
7
0
Order By: Relevance
“…However, the results of the present study showed that seed length, septum length, and the eventual presence and features of the seed wing are diagnostic characteristics for the genus Lepidium. This result is coherent with studies using seed characteristics for taxonomic studies in Lepidium (31,34,35).…”
Section: Discussionsupporting
confidence: 88%
“…However, the results of the present study showed that seed length, septum length, and the eventual presence and features of the seed wing are diagnostic characteristics for the genus Lepidium. This result is coherent with studies using seed characteristics for taxonomic studies in Lepidium (31,34,35).…”
Section: Discussionsupporting
confidence: 88%
“…The stubs were then coated with gold (Au) using an ion-sputtering device (Cressington Scientific Instruments 208HR; Watford, UK). The prepared floral organs and seeds were observed using a low voltage field emission scanning electron microscope (JEOL JSM-7000F; Tokyo, Japan) at an accelerating voltage of 15 kV with a working distance of 9–15 mm [53].…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study suggested that the morphological characteristics of reproductive organs, particularly testa ornamentation, can be used to distinguish between C. chinensis and C. japonica [ 60 ]. Recently, the availability of detailed seed micromorphology has provided valuable diagnostic characteristics for authenticating small medicinal seeds [ 51 , 52 ] and taxonomic identification [ 61 , 62 ]. In this study, micromorphological analysis using a scanning electron microscope revealed that Cuscuta seeds including CS (types I, II, and glabrous hilum) are easily distinguishable from the seeds of adulterant Perilla species (type III and glandular hairs on hilum).…”
Section: Discussionmentioning
confidence: 99%
“…Seeds are commonly used as traditional herbal medicines; however, commercial markets often sell mixed seeds from different species, including adulterants, within a single package, while some authentic medicinal seeds can be difficult to distinguish [ 49 , 50 ]. Therefore, multilateral approaches including microscopic analysis have been developed to authenticate and distinguish genuine species from congeneric species and adulterants such as Lepidii Seu Descurainiae Semen [ 51 ] and Pharbitidis Semen [ 52 ]. Microscopic authentication of medicinal materials has proven to be a highly reliable and accurate identification tool [ 8 , 51 , 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation